Unveiling the noxious effect of polystyrene microplastics in aquatic ecosystems and their toxicological behavior on fishes and microalgae - Jalaudin Basha, Nurin Nabilah; Adzuan Hafiz, Nurfarwizah Binti; Osman, Mohamed Syazwan; Abu Bakar, Noor Fitrah (Frontiers in Toxicology, 2023)
Microplastic (MP) particles are considered noxious pollutants due to their presence in aquatic habitats at almost every level of the food chain. Thus, the entry of MP particles into marine waterbodies has triggered a common research interest. Until recently, the toxicity of polystyrene towards aquatic creatures in comparison to other polymers has not been widely investigated. This article provides an extensive overview of the occurrence of microplastic particles, the route of polystyrene (PS) in the aquatic ecosystem, the PS properties characterization, and its noxious effects on the aquatic biota, particularly fishes and microalgae. Alarming high levels of polystyrene were found in urban, coastal, and rural surface waters and sediments. The fast-screening technique began with a stereoscope to determine the polystyrene particles’ shape, size, and color on the organism. SEM and complemented by micro FTIR or Raman spectroscopy were used to evaluate MP’s polymer structures. The findings present evidence suggesting that polystyrene buildup in fish can have long-term and unknown consequences. Meanwhile, the presence of polystyrene on microalgae causes a decrease in chlorophyll concentration and photosynthetic activity, which may disrupt photosynthesis by interfering with the electron characters and leading to the production of reactive oxygen species (ROS).